What's at Stake: Evaluating a Run-Hide-Fight® Intervention Video through the Lens of Vested Interest Theory. Issue 12 (1st December 2020) - Skurka, Chris; Reynolds-Tylus, Tobias; Quick, Brian; Hartman, Daniel
Abstract : The Department of Homeland Security and the Federal Bureau of Investigation have encouraged colleges and universities to create emergency preparedness interventions that prepare students, faculty, and staff for any conceivable campus crisis. In this investigation, we tested the efficacy of a professionally produced Run-Hide-Fight® video to accomplish such a goal with a convenience sample of college students. Drawing on Vested Interest Theory (VIT) to guide our evaluation, we observed significant gains in stake, salience, and self-efficacy for students exposed to the emergency preparedness video compared to those not exposed to the video. We find evidence not only for short-term gains immediately after message exposure but also persisting effects two weeks after exposure. In addition, greater perceptions of stake and salience in response to the video predicted more favorable attitudes toward emergency preparedness over time. These findings demonstrate the potential for brief messages shown in university classrooms to encourage students to feel vested in emergency preparedness on campus. They also shed light on promising messaging strategies to foster favorable attitudes toward emergency preparedness.